The variety of beliefs about the causes of safety among safety practitioners. (April 2022) - Carroll, John S.; Pfeiffer, Yvonne; Nowak, Hans; Friis, Simon
Highlights: Safety professionals perceive a wide variety of causes of safety. Safety professionals show little consensus about the most important causes of safety. Causes of safety can be grouped into a parsimonious yet meaningful list of 15 categories. Causal beliefs varied significantly across national and industry culture and reflective cognitive style. Abstract: Recent efforts to develop a knowledge base for safety professionals and practitioners recognizes that most safety work is based on a loose collection of principles from management, social science, and work experience. Safety professionals and practitioners encounter multiple approaches and safety regimes with considerable variation across time periods, countries, industries, organizations, occupations, and individuals. In this paper, we build a foundation for collaborative learning by characterizing and categorizing beliefs about the causes of safety among experienced safety practitioners and identifying sources of variation associated with demographic characteristics, work experience, and cognitive style. We conducted two surveys, the first relying primarily on open-ended questions and the second using selection from a list of causes of safety. Responses from the first survey were coded into 36 categories of causes. Notably, few causes were external to the operating organization. In the second survey, we added additional causes to create a list of 42 causes from which respondents could choose their most important causes. We found considerable variation among respondents, with even the most frequent safety causes given by fewer than 60% of respondents. We grouped the 42 causes into a parsimonious yet meaningful list of 15 higher-level cause categories. Causal beliefs varied by demographic characteristics, work experience, and cognitive style. To facilitate a collaborative learning process, we need to acknowledge variability in safety management approaches as a resource, respect and appreciate contributions from varied sources, and strengthen capabilities to converse across boundaries and more effectively develop and share knowledge.